Novel alkynyl substituted 3,4-dihydropyrimidin-2(1H)-one derivatives as potential inhibitors of chorismate mutase - Rao, V. Mallikarjuna (2013)
A series of novel alkynyl substituted 3,4-dihydropyrimidin-2(1H)-one (DHPM) derivatives were designed, synthesized and evaluated in vitro as potential inhibitors of chorismate mutase (CM). All these compounds were prepared via a multi-component reaction (MCR) involving sequential I2-mediated Biginelli reaction followed by Cu-free Sonogashira coupling. Some of them showed promising inhibitory activities when tested at 30 μM. One compound showed dose dependent inhibition of CM with IC50 value of 14.76 ± 0.54 μM indicating o-alkynylphenyl substituted DHPM as a new scaffold for the discovery of promising inhibitors of CM.